The Impact of Value Engineering on Material Selection: An Example from the Construction Industry - TARHAN, İBRAHİM ETHEM; QUFFA, BARAA (Springer Science and Business Media Deutschland GmbH, 2024)
The urgent need for Value Engineering has arisen due to the enormous expenditure in the construction industry, which could be reduced by up to 25%. This substantial spending is often accompanied by poor quality, leading to a constant need for reconstruction and maintenance. The methods and concepts of Value Engineering can be applied to address this issue. By using Value Engineering, solutions can be created that fulfil the same functional purpose at a lower cost while maintaining high quality. This can be achieved through an analytical study using a specific approach conducted by a multidisciplinary team to identify and classify the functions that the project performs. Profound methods can then be utilized to find innovative alternatives without compromising the basic requirements and quality. This research is dedicated to demonstrating the methodology of Value Engineering while highlighting its impact on construction projects through a case study: Magrabi Offices in Saudi Arabia. This paper used an organized multidisciplinary methodology to identify the project’s main and secondary functions, then utilized Pareto’s law to identify higher-cost materials. It was proven that finding low-cost equivalent materials could reduce the total price by 23.13%. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.
International Symposium for Production Research, ISPR 2023
Keywords: Construction Industry; Improving Quality; Low Cost; Project Development; Value Engineering